DIFFERENT TYPES OF COMPARISON OF LANGUAGE SYSTEM (PANCHRONIC, SYNCHRONIE) - Ergashboyeva Sabohat; N.Dusboyeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The Uzbek language is actively used in the political-legal, socio- economic, spiritual-educational spheres, and is heard on international forums. Attention to our language and interest in learning it is growing in foreign countries. This article provides information on different types of language system comparisons (panchronic, synchronic).